Measurement of bone thickness at the site of titanium miniplates used to retain nasal prostheses in fused computed tomographic data - Plath, Karim; Jung, Alexander; Rückschloß, Thomas; Möhlenbruch, Markus Alfred; Plinkert, Peter K.; Federspil, Philippe A. (The British journal of oral & maxillofacial surgery, 2020)
Our aim was to investigate the bone thickness at the site of titanium miniplates inserted to retain nasal prostheses. We studied 13 patients who had had titanium miniplates inserted for retention of nasal prostheses with a total of 60 titanium bone screws. A trajectory along each bone screw was segmented in fused computed tomographic (CT) data. Bone thickness was measured along this trajectory on the preoperative CT. The median bone thickness at the positions of the screws implanted on the frontal process of the maxillary bone was 1.4 (range 0.2-6.9) mm (mean 1.8). The median (range) values for men and women were 1.4 (0.2-6.9) mm and 1.3 (0.2-3.3) mm, respectively. The thickest bone was at the cranial part of the frontal process of the maxilla with a median of 2.0 (range 0.3-4.1) mm. However, differences in sex and position were not significant. None of the implant miniplates lost osseointegration. Despite the low bone stock at the lateral aspect of the pyriform aperture, survival of implanted titanium miniplates was 100% in this study group.